Systematic Literature Review (SLR): Implementation of Flip Classroom Using Learning Management System (LMS) to Improve Students' Learning Independence - Runiasih, Mawar; Rugaiyah, Rugaiyah; Ika, Linda (PT. BATARI EDU CALYA, 2025)
Digital learning began since the Covid-19 pandemic and because of the increasingly sophisticated development of the era, the education aspect has been affected to make changes towards digital, including in the learning process. This study aims to determine the application of flip classroom using a learning management system (LMS) to increase student independence. The method used in this study is a systematic literature review (SLR) by identifying and interpreting the overall research results obtained. The articles used in this study, as many as 20 national and international journal articles that are closely related to keywords obtained from Google Scholar with the help of the publish and perish application in 2017-2024. Article data is presented in the form of a table that includes the author's name, year of publication and research results which will later be analyzed and summarized into one complete discussion in this study. The results of this study based on a summary of 20 journals show that the application of flip classroom in the classroom using various LMS can increase student independence because it can make students more active, critical, and innovative.